Current Status of Renal Xenotransplantation and Next Steps. Issue 2 (18th February 2023) - Tector, Alfred J.; Adams, Andrew B.; Tector, Matt
Abstract : Renal transplantation is the preferred treatment of ESKD, but the shortage of suitable donor kidneys from the cadaver pool means that many patients with ESKD will not receive a kidney transplant. Xenotransplantation has long represented a solution to the kidney shortage, but the occurrence of antibody-mediated rejection has precluded its clinical development. Developments in somatic cell nuclear transfer in pigs and gene editing tools have led to the creation of new donor pigs with greatly improved crossmatches to patients. In addition, improvements in preclinical kidney xenotransplant survival using new anti-CD40/CD154–based immunosuppression have pushed xenotransplantation to the point where it is reasonable to consider initiating a clinical trial to evaluate this potential therapy in patients.